Pemberdayaan kelompok ibu rumah tangga sebagai kader bijak antibiotik dalam upaya pengendalian resistensi antibiotik tingkat komunitas - Farah Diba, Masayu; Amalia, Ella; Sabrina, Tia; Rivani, Erizka; Zanaria, Rima; Nawawi, Rizki Andini (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Infectious diseases are a threatening health problem in developing countries, including Indonesia. Diseases caused by bacterial infections can be overcome relatively easily after the discovery of various antibiotics. Uncontrolled use of antibiotics will trigger antibiotic resistance. With the incidence of antibiotic resistance, the potential of antibiotics will be reduced in treating infections and diseases in humans, animals and plants. Community service activities aim to provide knowledge to the community about antibiotics, how to use antibiotics wisely, and introduction to the concept of antibiotic resistance. The activities carried out were in the form of empowerment in the form of counseling for the community and assistance in the form of training for groups of prospective antibiotic wise cadres in the Siring Agung Village area. The results of this activity were obtained to increase the insight and knowledge of the community and health cadres about Antibiotic Wisdom, especially the use of antibiotics correctly, how to get them, how to follow up on antibiotic drug waste if it remains. In addition, the community and cadres also have the skills to wash hands properly and correctly using running water and soap independently to prevent transmission of infectious diseases. Furthermore, it is hoped that continuous service activities with similar themes at different layers or levels of society can be carried out in order for the community to know the importance of the principle of using antibiotics wisely so that the incidence of antibiotic drug resistance can be suppressed to increase.